Paranoplocephala nearctica Haukisalmi & Henttonen, 2007, n. sp. ... - Haukisalmi, Voitto; Henttonen, Heikki (Zenodo, 2007)
Paranoplocephala nearctica n. sp. (Figs. 3–4) Type host: Myodes rutilus, Myomorpha, the northern red-backed vole. Type locality: unnamed lake near North Fork of Koyukuk River, Gates of the Arctic National Park and Preserve (GAAR), northern Alaska, U.S.A., 67o27'11.2"N, 150o51'00.2"W. Site: Small intestine (duodenum or jejunum). Deposited specimens: Holotype: MSB Endo 1 (field code AF 61624), from My. rutilus (UAM 78325) collected on 23rd July 2002 at an unnamed lake near North Fork of Koyukuk River, Gates of the Arctic National Park and Preserve (GAAR), northern Alaska, U.S.A. (67o27'11.2"N, 150o51'00.2"W). Collectors: H. Henttonen, K. Hildebrandt, J. Laakkonen and J. Niemimaa. Paratype: MSB Endo 2 (field code AF 59966), from My. rutilus (UAM 79092), collected on 14th July 2002 at Agiak Lake, GAAR, Alaska (68o95'01.4"N, 152o57'36.2"W). Collectors as for the holotype. Voucher specimens: i) MSB Endo 4 (AF 59962), from My. rutilus (UAM 79088), Agiak Lake, GAAR, Alaska, ii) MSB Endo 7 (AF 61179), from My. ... : Published as part of Haukisalmi, Voitto & Henttonen, Heikki, 2007, A taxonomic revision of the Paranoplocephala primordialis (Douthitt) complex (Cestoda: Anoplocephalidae) in voles and squirrels, pp. 51-68 in Zootaxa 1548 on pages 58-62, DOI: 10.5281/zenodo.178029 ...